ASSESSMENT OF THE ACTUAL NUTRITIONAL STATE OF PREGNANT AND LACTATING WOMEN - Яков Яковлевич Яковлев; Фарок Каримович Манеров; Марина Михайловна Котович; Сергей Павлович Щепетков; Марина Афанасьевна Соколовская (The Publishing House Medicine and Enlightenment, 2020)
The aim of our study is to assess the actual implementation of the recommendations on the nutrition of pregnant and lactating women from both the medical staff and the women themselves. The study included 5753 women, of whom 5.6 % were pregnant and 94.4 % of mothers with children. Most of the respondents lived in Russia (n = 4977). The main sources of information on the nutrition of pregnant and lactating women were obstetrician-gynecologists and pediatricians. The study obtained data on the restriction of many foods during pregnancy and lactation both by doctors and women. The knowledge of doctors and women about the primary prevention of food allergies in children is insufficient, and therefore unjustified restrictions on the diet of women are prescribed. To maintain lactation, agents that have no evidence base are widely used. Conclusion. Our study showed that Russian and international recommendations on the nutrition of pregnant and lactating women are not actually implemented either by health workers or pregnant and lactating women.